2018
DOI: 10.1002/slct.201801287
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationships for Poly(phenylene)vinylene Derivatives as Antibacterial Agents

Abstract: A series of poly(phenylene)vinylene (PPV) derivatives with different geometries and peripheral functional groups have been synthesized by Horner‐Wadsworth‐Emmons reaction. Compounds bearing carboxylic acid or quaternary ammonium functional groups prepared by this metal‐free protocol were weakly active against both Gram‐negative and Gram‐positive bacteria, which is in contrast to previously reported results. The activity of polyanionic derivatives was higher for Gram‐negative bacteria and showed bacteriostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…ones (Tolosa et al, 2018). In addition, the antifungal activity on planktonic and sessile forms of C. tropicalis was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ones (Tolosa et al, 2018). In addition, the antifungal activity on planktonic and sessile forms of C. tropicalis was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the OSBs was carried out using a methodology described previously based on the reaction of Horner-Wadsworth-Emmons (Tolosa et al, 2018). From a structural point of view, compound OSB 1 is characterized as an anionic molecule at the pH value where the biological experiments described below are performed, whereas OSB 2 and 3 have a cationic character (inset Figure 1).…”
Section: Osb Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ortega et al prepared and studied anilinium‐terminated carbosilane dendrimers and showed that they were effective against Staphylococcus aureus and Escherichia coli . Very recently, Tolosa et al examined the biocidal activity of poly(phenylene)vinylene derivatives with different geometries and peripheral functional groups, including the aniline derivatives. These latter compounds only exhibit moderate activity; however, these two reports demonstrate the importance of multivalence and provide sufficient motivation for further exploration of the biocidal behavior of anilinium‐containing macromolecules.…”
Section: Introductionmentioning
confidence: 99%